How do you simplify #((m^2)^2z^3zd)/(mz^5d^3)#?

1 Answer
Feb 1, 2017

Answer:

#(m^3)/(zd^2)#

Explanation:

Simplify #((m^2)^2z^3zd)/(mz^5d^3)#.

First apply power rule #(b^m)^n=b^(m*n)#.

#(m^((2*2))z^3zd)/(mz^5d^3)#

#(m^4z^3zd)/(mz^5d^3)#

Apply product rule #a^ma^n=a^((m+n)).#
(Reminder: #b=b^1#).

#(m^4z^3z^1d)/(mz^5d^3)#

#(m^4z^((3+1))d)/(mz^5d^3)#

Simplify.

#(m^4z^4d)/(mz^5d^3)#

Apply quotient rule #a^m/a^n=a^((m-n))#.

#m^((4-1))z^((4-5))d^((1-3))#

Simplify.

#m^3z^(-1)d^(-2)#

Apply negative exponent rule #a^(-m)=1/a^m#.

#(m^3)/(zd^2)#